ZAMANAGÓY SPORTTA JAS SPORTSHÍLARDÍ TAŃLAW MASHQALALARÍ - Ramazanov, M.B. (SCIENCE and SOCIETY, 2021)
The article is devoted to the selection and orientation of young talented athletes in sports. It will be discussed the concept of athlete selection, stages of selection and tasks. Information on the trend towards rejuvenation in sports.